2018
DOI: 10.1039/c8ra02258e
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in biochar-supported photocatalysts: synthesis, role of biochar, and applications

Abstract: Incorporating photocatalytic nanoparticles with biochar templates can produce biochar-supported photocatalysts (BSPs) and combine the advantages of biochar with catalytic nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(67 citation statements)
references
References 85 publications
3
64
0
Order By: Relevance
“…Photocatalysis has emerged into an efficient and viable technique for purification of wastewater. Various nanoparticles such as TiO 2 , RuO 2 , SiO 2 , ZrO 2 , ZnO, CdS, and ZnS have been used as semiconductor photocatalysts [1]. Despite the excellent functionality, high photostability, and non-toxicity properties, the quick recombination of hole-electron pairs and poor visible-light response limit the photocatalytic performance of semiconductors [2].…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis has emerged into an efficient and viable technique for purification of wastewater. Various nanoparticles such as TiO 2 , RuO 2 , SiO 2 , ZrO 2 , ZnO, CdS, and ZnS have been used as semiconductor photocatalysts [1]. Despite the excellent functionality, high photostability, and non-toxicity properties, the quick recombination of hole-electron pairs and poor visible-light response limit the photocatalytic performance of semiconductors [2].…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at the appreciation of this residue, using a waste for the removal of environmental pollutants. 13,14,19,20 MDF biochar provides porosity to the composite, increasing surface area, facilitating material removal from the solution for later recycling, reducing material loss in the solution, improving photocatalytic properties. To date there are no reports in the literature of the use of MDF biochar as a support for TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…2. In this study, PO 4 3− ions from phosphoric acid and Ag + ions from silver-ammonia complex reacted to form Ag 3 PO 4 . Interestingly, it was found that tetrapod-like and dodecahedron-like Ag 3 PO 4 can only be found between 0.5 and 1 of phosphoric-acid-to-ammonia ratios.…”
Section: Resultsmentioning
confidence: 91%
“…Introduction: Visible-light induced photocatalysis is gaining an increasing attention as a promising wastewater treatment alternative in degrading dye stuff and eradicating pathogens since the photocatalytic activity of N-doped TiO 2 was discovered and exploited [1][2][3]. Many research efforts were made and new materials were invented to overcome the potential high operation cost from inefficient photolytic charge separation of N-doped TiO 2 [4][5][6]. In 2010, silver orthophosphate (Ag 3 PO 4 ) with high photo-oxidative activity for O 2 evolution from water and the degradation of organic pollutants was prepared by Yi et al, creating a need for better understanding on the principle of Ag 3 PO 4 photocatalysis [7].…”
mentioning
confidence: 99%